Development of a tissue-regenerative vascular graft: Structural and Mechanical Aspects - Sirry, Mazin Salaheldin (Department of Human Biology, 2014)
In attempt to prevent graft failure, the tissue-regeneration field offered the porous vascular scaffolds as promising solution for the lack of endothelialization seen in the small-calibre synthetic vascular graft. Another cause of graft failure was reported to be the mechanical mismatch between the graft and the host vessel. This study concerned the investigation and optimization of structural designs of tissue-regenerative vascular grafts, comprising ingrowth permissible porous polyurethane (PPU) foam and knitted reinforcement wire mesh, with the aim of providing vascular prostheses that mimic arterial mechanics. A 3D geometry of a knitted eight-loop wire mesh was imported into Abaqus CAEÂ® 6.8-2 and assembled with a PPU tube geometry such that the wire mesh acted as external reinforcement (EX) or embedded reinforcement (EM) to the PPU tube. A 45Â°-section assembly was meshed using 8-node linear brick elements. Nitinol (NITI) and polyurethane (PU) material models were used for the knitted mesh. Material parameters obtained in experimental tests were implemented in hyperfoam (PPU), shape memory alloy (NITI) and linear elastic (PU) constitutive models. The luminal grafts surfaces were subjected to uniformly distributed pressure load ramping from 0 to 200mmHg. Models were compared in terms of predicted maximum stress and strain, wall compression, strain energy, radial displacement and compliance. The predicted radial compliance ranged between 1.2 and 15.6%/100mmHg in the reinforced grafts, compared to 106.4 and 65.1%/100mmHg for the non-reinforced grafts. The maximum stress in the Nitinol remained safe at 33 % of stress associated with start of austenite-martensite phase transformation (i.e. 483MPa). The maximum stress and strain values detected in the PPU tube indicated recoverable elastic deformation. The reinforcement enhanced the mechanical performance of the graft without affecting its tissue-regenerating characteristics, as the predicted maximum wall compression indicated that the reduction in size of pore windows would still allow ingrowth of capillaries and arterioles.